Albania : Joint Staff Assessment of the Poverty Reduction Strategy Paper-Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2003)
The Joint Staff Assessment (JSA) reviews the first Annual Progress Report of its Poverty Reduction Strategy paper, known in Albania as the National Strategy for Socio-Economic Development (NSSED). The JSA noted that the first year's performance in implementing the NSSED is satisfactory, and the Progress Report, despite weaknesses, is acceptable. The staff of the World Bank and IMF considers that the country's efforts toward implementation of the strategy provide sufficient evidence for its continuing commitment to poverty reduction, and therefore the strategy continues to provide a credible framework for Bank and IMF concessional assistance.